FDI and economic growth in Africa : the case of Morocco - (:unkn) unknown (My University, 2023)
From the beginning of the 1980s, Morocco, like other emerging countries, organized a set of measures and reforms working in favor of the attractiveness of FDI.FDI represents the “bridge” for African countries to integrate into and be part of the international financial and commercial sphere.Morocco is aware of the role of FDI in economic growth, it has embarked on a project of structural, institutional and regulatory reforms and changes in order to ensure their attractiveness.The presence of FDI in an economy symbolizes an open and efficient internationalized economic system and acts as an engine of economic growth.Through this study, we will demonstrate the effects of FDI on the economic and social growth of Morocco, via an analysis of macroeconomic indicators, to conclude with recommendations drawn on the basis of the practices of pioneering countries in the attraction of FDI. FDI remains a determining factor and a had a degree of influence on the economic growth of Morocco, which is positioned among others such as the promotion of local investment, the development of human capital, etc.
Keywords: African Research